2013
DOI: 10.1111/bjd.12467
|View full text |Cite
|
Sign up to set email alerts
|

Association ofNLRP1genetic variants and mRNA overexpression with generalized vitiligo and disease activity in a Gujarat population

Abstract: SummaryBackground It has been suggested that NLRP1 is involved in susceptibility to a wide range of autoimmune diseases including generalized vitiligo (GV). Genetic polymorphisms in the gene encoding NLRP1 (previously known as NALP1) have previously been shown to be associated with GV and there is speculation about their involvement in the regulation of NLRP1 expression. Objectives To explore NLRP1 polymorphisms and investigate their association with NLRP1 mRNA expression and disease activity in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 46 publications
(94 reference statements)
0
24
0
Order By: Relevance
“…NLRP1 is a key regulator of the innate immune system, particularly in the skin and the NLRP1 inflammasome promotes caspase 1 dependent cleavage of IL1B precursor in to bioactive IL1B, resulting in IL1B secretion and downstream inflammatory responses. Interestingly, our recent study shows significant association of NLRP1 promoter variants with GV and NLRP1 overexpression in patients compared to controls; which might lead to increased IL1B production in vitiligo patients [67].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…NLRP1 is a key regulator of the innate immune system, particularly in the skin and the NLRP1 inflammasome promotes caspase 1 dependent cleavage of IL1B precursor in to bioactive IL1B, resulting in IL1B secretion and downstream inflammatory responses. Interestingly, our recent study shows significant association of NLRP1 promoter variants with GV and NLRP1 overexpression in patients compared to controls; which might lead to increased IL1B production in vitiligo patients [67].…”
Section: Discussionmentioning
confidence: 83%
“…Our previous studies suggest that susceptibility to generalized vitiligo involves a number of immune regulatory genes such as cytotoxic T-lymphocyte associated antigen-4 ( CTLA 4), human leukocyte antigen ( HLA ), interleukin-4 ( IL 4), tumor necrosis factor-α ( TNFA ), tumor necrosis factor-β ( TNFB ), interferon-gamma ( IFNG ), melanocyte proliferating gene 1 ( MYG1 ), and NACHT leucine-rich-repeat protein 1 ( NLRP1 ) [59][67]. For the first time we report an association between IL1B promoter polymorphism and vitiligo along with higher transcript levels of IL1B in vitiligo patients as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Besides gain-of-function mutations of inflammsome proteins, a functional NLRP1 promoter polymorphism resulting in elevated gene expression was associated with increased susceptibility towards rheumatoid arthritis [80] and generalized vitiligo [81]. …”
Section: Production Of Il-1β Requires Two Distinct Signalsmentioning
confidence: 99%
“…NACHT leucine-rich repeat protein 1 (NLRP1), known to be involved in inflammation and apoptosis [170,171], modulates the response of cells towards proinflammatory cytokines such as IL1β, IFNγ and TNFα. Recently, we have found increased expression of NLRP1 in vitiligo patients [172]. Bassiouny et al [173] have found increased level of IL17 and its positive correlation with disease pregression in both the lesional skin and sera of vitiligo patients.…”
Section: Autoimmunity In Vitiligomentioning
confidence: 79%
“…Most vitiligo susceptibility loci encode melanocyte components, and antioxidant and immune-regulatory proteins [40,246]. For example, associations have been established between vitiligo pathogenesis and polymorphisms in tyrosinase (TYR) [247], catalase (CAT) [65], glutathione peroxidase (GPX) [65], melanocortin 1 receptor (MC1R) [248], major histocompatibility complex (MHC) [249], NACHT leucine-rich repeat protein 1 (NLRP1) [172] [252]. Both protective and susceptibility-increasing effects have been found in the case of different polymorphisms in these genes [253,254].…”
Section: Cross Talk Between Oxidative Stress Er Stress and Immune Symentioning
confidence: 99%